KAJIAN INTERTEKSTUAL: NOVEL DIKTA DAN HUKUM DENGAN NOVEL ANGKASA DAN 56 HARI: KAJIAN INTERTEKSTUAL: NOVEL DIKTA DAN HUKUM DENGAN NOVEL ANGKASA DAN 56 HARI - SAFITRI, LINDRIANA Safitri (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2024)
Intertextual theory views a literary work as something that has a relationship with the previous text. Literary works have their own beauty that can attract someone to enjoy them from different points of view. The approach in this research uses intertextual studies to analyze data in order to see the relationship between the two texts. The data source in this research is based on the novels Dhia'an Farah Afifah and Destashya Wisna Diraya Putri. Dhia'an Farah Afifah is one of the writers who raised the theme of romance in one of his novels entitled Dikta and Hukum which was adapted from Alternate Universe Twitter (AU) which was later published as a novel. However, the love story raised in this story is not only about stories that the ending is happy, just like Dhia'an Farah, Destashya Wisna Diraya Putri also raises the same theme, namely about love, which is outlined in her novel entitled Angkasa and 56 Days which is based on Alternate Universe Twitter (AU). The novel Dikta and Hukum has Dikta as the male character and Nadhira as the female main character. The love story of Dikta and Nadhira was forced to stop when Dikta died due to the disease he was suffering from, namely kidney failure. The novels Angkasa and 56 Days have the main characters Angkasa as the male character and Nadhine as the main female character. Their love story first occurred during the introduction to campus life, starting with the word "hi" which apparently made them fall in love with each other.